Which equation has the solution x=3?

9 answers

There are infinitely many equations that can have \( x = 3 \) as a solution. Here are a few examples:

  1. \( x - 3 = 0 \)
  2. \( 2x - 6 = 0 \)
  3. \( x^2 - 9 = 0 \)
  4. \( 3x - 9 = 0 \)
  5. \( \frac{x}{3} - 1 = 0 \)

Each of these equations can be solved to find that \( x = 3 \) is a solution. If you have a specific type of equation in mind or constraints, please provide more details!

Which equation has the solution x=3?

A. 2x -, 2 =4

B. 6x - 4 = 86

C. 7x - 7 = -14

D. 8x + 2 =46

To determine which equation has the solution \( x = 3 \), we can substitute \( x = 3 \) into each equation and check if they hold true.

A. \( 2x - 2 = 4 \)
Substituting \( x = 3 \):
\[ 2(3) - 2 = 6 - 2 = 4 \] (True)

B. \( 6x - 4 = 86 \)
Substituting \( x = 3 \):
\[ 6(3) - 4 = 18 - 4 = 14 \] (False)

C. \( 7x - 7 = -14 \)
Substituting \( x = 3 \):
\[ 7(3) - 7 = 21 - 7 = 14 \] (False)

D. \( 8x + 2 = 46 \)
Substituting \( x = 3 \):
\[ 8(3) + 2 = 24 + 2 = 26 \] (False)

The equation that has the solution \( x = 3 \) is A. \( 2x - 2 = 4 \).

Which equation has the solution x=6

A. 3x + 5 =38

B. 9x - 4 = -50

C. 6x + 1 = 37

D. 8x + 8 =28

To determine which equation has the solution \( x = 6 \), we will substitute \( x = 6 \) into each equation and check for correctness.

A. \( 3x + 5 = 38 \)
Substituting \( x = 6 \):
\[ 3(6) + 5 = 18 + 5 = 23 \] (False)

B. \( 9x - 4 = -50 \)
Substituting \( x = 6 \):
\[ 9(6) - 4 = 54 - 4 = 50 \] (False)

C. \( 6x + 1 = 37 \)
Substituting \( x = 6 \):
\[ 6(6) + 1 = 36 + 1 = 37 \] (True)

D. \( 8x + 8 = 28 \)
Substituting \( x = 6 \):
\[ 8(6) + 8 = 48 + 8 = 56 \] (False)

The equation that has the solution \( x = 6 \) is C. \( 6x + 1 = 37 \).

What value of x makes the equation below true?

6x + 1 = 19

A. 1

B. 10

C. 3

D. 11

To find the value of \( x \) that makes the equation \( 6x + 1 = 19 \) true, we can solve for \( x \).

Starting with the equation:

\[ 6x + 1 = 19 \]

  1. Subtract 1 from both sides:

\[ 6x = 19 - 1 \]

\[ 6x = 18 \]

  1. Divide both sides by 6:

\[ x = \frac{18}{6} \]

\[ x = 3 \]

So the value of \( x \) that makes the equation true is C. 3.

What value of z makes the equation below true?

7z - 3 = 4

A. 1

B. 5

C. 4

D. 14

To find the value of \( z \) that makes the equation \( 7z - 3 = 4 \) true, we can solve for \( z \).

Starting with the equation:

\[ 7z - 3 = 4 \]

  1. Add 3 to both sides:

\[ 7z = 4 + 3 \]

\[ 7z = 7 \]

  1. Divide both sides by 7:

\[ z = \frac{7}{7} \]

\[ z = 1 \]

So the value of \( z \) that makes the equation true is A. 1.